The Condition of Sealing Waterproofing Materials Used in The Construction and Repair of Roads, And Their Requirements - B.A.Mamadov (Genius Journals, 2023)
It is known that the widespread use of asphalt concrete and petroleum mineral coatings in Uzbekistan is complicated, especially in recent years, due to their insufficient shear resistance at high summer and crack resistance at low winter negative temperatures.
Keywords: asphalt concrete; negative temperatures; bitumen; composition